The Effectiveness of Endoscopic Surgery of Juvenile Angiofibroma Using Surgical Glue - Ardesan, Seyed-Hadyi Samimi; Ardehali, Mojtaba Mohammadi; Doustmohammadian , Najmeh (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: The current study aimed to provide a method for juvenile nasopharyngeal angiofibroma embolization using Glubran glue in patients with low stage tumor. This method not only has less blood loss and good visualization but also impose a low cost, where no pre-operative embolization complications were found for this procedure. METHODS: Between 2012 and 2014, 30 patients with angiofibroma undergoing endoscopic surgery. Age, sex, tumor stage, average blood loss, complications, length of hospitalization, and recurrence rate of the tumor were the main measured outcomes. Furthermore, 30 patients were divided into three groups with matched age, sex, and tumor staging. Group 1 received glue (Glubran), while Group 2 selected for study without glue and embolization and pre-operative embolization was considered for Group 3. RESULTS: Based on the amount bleeding, the mean blood hemorrhage in Groups 1, 2, and 3 was 510, 1655, and 800 ml, respectively, the difference of hemorrhage between Groups 1 and 2 was found to be statistically significant (p = 0.007). Blood loss in Group 1 was found to be less than Group 3, but the difference of hemorrhage between Group 1 and 3 was not statistically significant (p = 0.678). No blood transfusion and complication were recorded for individuals in Group 1. The recurrence was found in 1 patient (10%) in both groups of 2 and 3, and no patient (0%) in Group 1. CONCLUSIONS: The direct intraoperative embolization technique with glue was capable of providing a more complete and targeted embolization of the tumor. Some advantages can be mentioned for this technique, including decreased blood loss, less radiation exposure, lower rates of complications, and recurrence, as well as shorter hospitalization time, the ease of procedure with a spinal needle and low cost.